2009
DOI: 10.1007/s11249-009-9459-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZrO2 Nanoparticles Additive on the Tribological Behavior of Multialkylated Cyclopentanes

Abstract: Monodisperse ZrO 2 nanoparticles with a particle size of about 6-7 nm and low volatile multialkylated cyclopentanes (MACs) lubricant were prepared and characterized. The effect of ZrO 2 nanoparticles as additive on the friction and wear behavior of MACs base oil was investigated. The friction and wear performance of 2 wt% ZrO 2 nanoparticles ? MACs was evaluated using an Optimal SRV oscillating friction and wear tester, with a steel ball sliding against the same steel counterpart disc. Results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Multialkylated cyclopentanes can support zirconia in tribological processes. A hard, protective ceramic-like tribofilm was formed on the surfaces prevented severe wear, seizure and damped the tribological impacts [15]. Zirconia doped lubricant showed lower wear rates and enabled to increase the maximum contact pressure (extreme pressure) compared to the reference.…”
Section: Zirconium-dioxde Particles As Lubricant Additivementioning
confidence: 99%
“…Multialkylated cyclopentanes can support zirconia in tribological processes. A hard, protective ceramic-like tribofilm was formed on the surfaces prevented severe wear, seizure and damped the tribological impacts [15]. Zirconia doped lubricant showed lower wear rates and enabled to increase the maximum contact pressure (extreme pressure) compared to the reference.…”
Section: Zirconium-dioxde Particles As Lubricant Additivementioning
confidence: 99%
“…In tribology, some nanomaterials were added into lubricating oil/grease to improve extreme pressure, anti-wear and friction-reduction properties [1]. In particular, the tribological properties of metals [2][3][4][5][6][7][8], metal oxides [9][10][11][12][13][14][15], metal sulphides [16][17][18][19], rare earth compounds [20][21][22][23][24], and borides [25][26][27][28] used as lubricating additives have been investigated. They can greatly improve the anti-wear and extreme pressure properties, reduce friction coefficient, and even retard the thermoinduced oxidation of lubricating oil/grease.…”
Section: Introductionmentioning
confidence: 99%
“…Since the friction‐enhancing components directly affect the properties of the friction surface, it is usually necessary to strictly control the content of the friction‐enhancing components in order to create sufficient shear force when sliding friction occurs with the counterpart surface and to reduce brake disc scratching. It has been established that introducing ZrO 2 particles in the suitable proportion can significantly enhance the friction stability and load‐bearing capability of materials 25 . Vlastimil et al 26 discovered that adding SiC to the friction material improved the COF and the wear resistance, and that 3.4% SiC was the optimal amount to add.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that introducing ZrO 2 particles in the suitable proportion can significantly enhance the friction stability and load-bearing capability of materials. 25 Vlastimil et al 26 discovered that adding SiC to the friction material improved the COF and the wear resistance, and that 3.4% SiC was the optimal amount to add. Xing et al 27 reported that the addition of 2% SiO 2 particles with a 120 nm diameter reduced the wear rate of the composite material by a ratio of 2-10.…”
Section: Introductionmentioning
confidence: 99%